Third Five Year Plan Government of Rajasthan - Planning Commission (Planning Commission)
Rajasthan is the second largest State in India in terms of area. It extends over 1.32 lakh sq. miles. Thus, the geographical area represents 12% of the total area of the country. It is bounded on the west and northwest by Pakistan, on the north and north-east by Punjab and Uttar Pradesh, on the south-east by Madhya Pradesh and on the south-west by Gujrat.
Government of Rajasthan, Planning Department